PENGARUH PEMERIKSAAN PAJAK, KESADARAN WAJIB PAJAK DAN DAN SURAT TAGIHAN PAJAK TERHADAP PENERIMAAN PAJAK ORANG PRIBADI - Inggit Purnama Sari (Yayasan Kayyis Mulia Jaya, 2025)
ABSTRACT This study aims to analyze the influence of tax audits, taxpayer awareness, and taxbills on individual income tax revenue. The study collected data throughquestionnaires from a sample of individual taxpayers. The analysis method used ismultiple linear regression, supplemented with descriptive statistics to describe thecharacteristics of the data. The results of the F test show a significant value of0.000, indicating that the overall regression model is significant, which means thatthe independent variables have a simultaneous effect on variable Y. Meanwhile, theresults of the t test show that the variables tax audits have a negative impact onindividual income tax revenue. This suggests that a high intensity of tax audits maycause discomfort or dissatisfaction among taxpayers, which in turn negativelyaffects tax revenue. Conversely, taxpayer awareness has a significant positiveinfluence, indicating that increased understanding and compliance with taxobligations can enhance tax revenue. Meanwhile, tax bills also show a negativeimpact on tax revenue, suggesting that this method may be less effective inencouraging increased tax payments. This research contributes to the governmentand related parties in understanding the factors influencing individual income taxrevenue. The recommendations from this study include the need for more effectiveand educational approaches to increase taxpayer awareness, as well as theexpansion of more humane strategies in the tax audit process and the issuance oftax bills. Keywords: Tax Revenue, Taxpayer Awareness, Tax Audit.